1980
DOI: 10.1007/bf00403197
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced changes in respiratory pathways and mitochondrial structure during microcycle conidiation of Neurospora crassa

Abstract: Changes in both respiratory pathways and mitochondrial structure of Neurospora crassa occurred under conditions of microcycle conidiation. Upon heat-treatment at 46 degrees C, conidia developed a highly cyanide-insensitive, hydroxamate-sensitive respiration associated with morphological alterations in mitochondrial membranes; such changes were time-dependent. When heat-treated conidia were shifted down to 25 degrees C, the alternate, hydroxamate-sensitive respiration decreased significantly, paralleling the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…S. cerevisiae grown on the nonfermentable substrate acetate continued to synthesize heat shock proteins indefinitely at the high temperature (28). Michea-Hamzehpour et al (34) have reported that heat-treated N. crassa conidia utilize an alternate pathway of respiration that is inhibited by salicylhydroxamic acid but not by cyanide (23), and we have confirmed this in our laboratory (data not shown). It is possible that the ability of N. crassa to switch from the normal cyanide-sensitive pathway of respiration to the alternate, noncytochrome-mediated pathway is related to the transiency of its heat shock response.…”
Section: Discussionsupporting
confidence: 86%
“…S. cerevisiae grown on the nonfermentable substrate acetate continued to synthesize heat shock proteins indefinitely at the high temperature (28). Michea-Hamzehpour et al (34) have reported that heat-treated N. crassa conidia utilize an alternate pathway of respiration that is inhibited by salicylhydroxamic acid but not by cyanide (23), and we have confirmed this in our laboratory (data not shown). It is possible that the ability of N. crassa to switch from the normal cyanide-sensitive pathway of respiration to the alternate, noncytochrome-mediated pathway is related to the transiency of its heat shock response.…”
Section: Discussionsupporting
confidence: 86%
“…For example, in Sclerotinia sclerotiorum, AOX participates in the regulation of growth, development, and responses to oxidative stress (48). In Aspergillus fumigatus and Neurospora crassa, cyanideinsensitive respiration catalyzed by AOX is induced by heat shock and oxidative stress (49,50). This study showed that the resistance of OE-aox strains to heat stress was significantly stronger than that of the WT strain.…”
Section: Discussionmentioning
confidence: 74%
“…Under these new conditions, we obtained a greater proportion of mitochondria with a density of 1 195 g ml-l, similar to that of mycelial mitochondria (Michea-Hamzehpour et al, 1979), than with a density of 1-212g ml-l, previously considered as characteristic of conidia (Ortega Perez et al, 1977). This mitochondrial heterogeneity might arise directly from the increased recovery and improved preservation of the mitochondria.…”
Section: Discussionmentioning
confidence: 77%
“…They were also clearly distinguishable from those isolated from mycelia (Michea-Hamzehpour et al, 1979).…”
Section: Discussionmentioning
confidence: 93%